Combined inhibition of ribonucleotide reductase and WEE1 induces synergistic anticancer activity in Ewing’s sarcoma cells - Judy Ziener; Julián Andrés Henao-Restrepo; Johanna Leonhardi; Max-Johann Sturm; Sabine Becker; Diana M. Morales-Prieto; Till Milde; James F. Beck; Jürgen Sonnemann (BMC Cancer)
Abstract Background Ewing’s sarcoma is a childhood bone and soft tissue cancer with poor prognosis. Treatment outcomes for Ewing’s sarcoma patients have improved only modestly over the past decades, making the development of new treatment strategies paramount. In this study, the combined targeting of ribonucleotide reductase (RNR) and WEE1 was explored for its effectiveness against Ewing’s sarcoma cells. Methods The RNR inhibitor triapine and the WEE1 inhibitors adavosertib and ZN-c3 were tested in p53 wild-type and p53 mutant Ewing’s sarcoma cells. The combination of adavosertib with the PARP inhibitors olaparib and veliparib was tested for comparison. Combinatorial effects were determined by flow cytometric analyses of cell death, loss of mitochondrial membrane potential and DNA fragmentation as well as by caspase 3/7 activity assay, immunoblotting and real-time RT-PCR. The drug interactions were assessed using combination index analysis. Results RNR and WEE1 inhibitors were weakly to moderately effective on their own, but highly effective in combination. The combination treatments were similarly effective in p53 wild-type and p53 mutant cells. They synergistically induced cell death and cooperated to elicit mitochondrial membrane potential decay, to activate caspase 3/7 and to trigger DNA fragmentation, evidencing the induction of the apoptotic cell death cascade. They also cooperated to boost CHK1 phosphorylation, indicating augmented replication stress after combination treatment. In comparison, the combination of adavosertib with PARP inhibitors produced weaker synergistic effects. Conclusion Our findings show that combined inhibition of RNR and WEE1 was effective against Ewing’s sarcoma in vitro. They thus provide a rationale for the evaluation of the potential of combined targeting of RNR and WEE1 in Ewing’s sarcoma in vivo.